Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)
À l'instar du public en général et des auditeurs qui ont suivi l'évolution de la carrière de Maryvonne Kendergi, n'y a-t-il pas lieu de s'interroger sur celle qui a donné un élan essentiel à la musique savante et contemporaine au Québec en permettant à la musicographie québécoise de sortir de l'emprise traditionnellement imposée par la critique musicale européenne?
Keywords: DIG; amériques; arts; biographie; discipline; histoire des femmes*; histoire et politique; musique; québec; régions géographiques; thématiques

The art of history African American women artists engage the past - Collins, Lisa Gail (Rutgers University., 2002)
In this lively and engaging book, Lisa Gail Collins examines the work of contemporary African American women artists. Her study comes at a time when an unprecedented number of these artists-photographers, filmmakers, painters, installation and mixed-media artists-have garnered the attention and imagination of the art-viewing public. To better understand the significance of this particular historical moment in American visual arts, Collins focuses on four "problems" that recur when these artists confront their histories: the documentation of truth; the status of the black female body; the relationship between art and cultural contact and change; and the relationship between art and black girlhood. By examining the social and cultural histories which African American women artists engage, Collins illuminates a dialogue between past and present imagemakers. The Art of History is a major contribution to the study of American visual culture. It will be of use to both scholars and students in art history, African American studies, American studies, and women's studies.
Keywords: afro-féminisme; amériques; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; fem1000; femmes* afro-américaines; féminisme afroaméricain; féminismes noirs; pratiques féministes; premier cycle; régions géographiques; thématiques; états-unis

Explorations in contemporary feminist literature: The battle against oppression for writers of color, lesbian and transgender communities - Pernal, Mary (P. Lang, 2002)
Explorations in Contemporary Feminist The Battle Against Oppression for Writers of Color, Lesbian and Transgender Communities is a work that bridges issues of oppression across diverse communities within the contemporary feminist movement. Fictional writings by authors such as Toni Morrison, Maya Angelou, Rose Tremain, and others are addressed in regard to their content of social messages. The major focus of this book is the need for personal-redefinition by members of marginalized communities seeking a ground of self-determination and respect, as expressed by various authors. The connections between authors' perspectives are rasied and a critical gaze is directed at the claim that personal choice equates with freedom.
Keywords: afro-féminisme; amériques; approches et analyses; arts; classisme; discipline; intersectionnalité; littérature; personnes lesbiennes; personnes trans*; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires